Development of cross-linked enzyme aggregates (CLEA)-amylase from super mealworm (Zophobas morio) - Muhammad Noor bin Easa (Kuliyyah of Engineering, International Islamic University Malaysia, 2016)
Super mealworm is a larva stage of darkling beetle insect. Studies of super mealworm have revealed that it contains a lot of protein content and hydrolases are one of the products which could be extracted from it. Due to instability of biocatalyst in industry, Cross- Linked Enzyme Aggregates (CLEA) as an immobilization technology has been found as a powerful tools to improve the performance of enzymes. The aim of this research is to explore the extraction process of hydrolases from super mealworm, followed by optimizing the immobilization process through CLEA. The screening of four hydrolases enzyme from super mealworm was done and the results showed that amylase has the highest enzymatic activity. The optimum condition for amylase extraction was studied using One Factor at A Time (OFAT) and Response Surface Methodology (RSM) under Face Centred Central Composite Design (FCCCD). The preparation of CLEA- amylase was also optimized using the same technique based on three important parameters; concentration of acetone, glutaraldehyde and Bovine Serum Albumin (BSA), respectively. The characterization of free and CLEA- amylase regarding stability, reusability and kinetics were studied and finally CLEA- amylase was applied as a detergent. The highest amylase activity was achieved under conditions of using 72 % (w/v) of sample: buffer ratio and pH buffer of 6.12, regardless of blending time. In terms of CLEA- amylase preparation, the optimum condition was achieved when using 65% (v/v) acetone and 90 mM glutaraldehyde concentration which could resulted in 28% of CLEA- amylase recovery activity. In contrast, BSA was found to have insignificant effect. The optimal reaction temperature and pH value in enzymatic reaction for both free and CLEA were found to be 45°C at pH 7 and 55°C at pH 11, respectively. It was also found that the immobilized enzyme could retain almost 15% of its activity after six cycles of reuse. Besides that, to determine kinetic parameters (Vmax and KM) in the free and CLEA- amylase, Michaelis- Menten kinetic models were applied using Hyperbolic Regression Software (3.95). Both Vmax (1.068 vs 17.23 mM/ min) and KM (0.182 vs 2.47 mM) values were lower after the immobilization process. Lastly, CLEA- amylase was applied in a detergent test and showed high stability against several detergent components and alkalinity agents. The addition of CLEA- amylase in commercial detergent formulation also had improved the removal of potato curry stains on white cloths. In short, this study could be a stepping stone for the production of immobilized amylase in large scale so that it could be used in wide industrial applications. Future studies should incorporate different types of precipitating agents, as well as the cross- linker to further optimize the CLEA preparation.